Cross-cultural adaptation and psychometric validation of a Chinese self-intermittent catheterization quality of life scale among patients with neurogenic bladder - Tang,Rong; Zhou,Liqiong (PeerJ, 2024)
Background Intermittent self-catheterization (ISC) is widely considered the gold standard for treating patients with neurogenic bladder (NB). Healthcare professionals and catheter users must optimize ISC care to improve patients’ quality of life. To achieve this, the Intermittent Self-Catheterization Questionnaire (ISC-Q) is a valuable tool with clear and easy-to-understand items. However, this scale has yet to be adapted for use in China, and its reliability and validity need to be tested through cross-cultural adaptation. Objectives The objective of this study was to culturally adapt the ISC-Q and develop the Chinese version of the ISC-Q (C-ISC-Q), and assess its reliability and validity among patients with NB. Methods With the authorization of the ISC-Q author, the Beaton mode was used to adapt the scale cross-culturally. The study was conducted from June 2020 to June 2021 in three phases: committee-based translation from English to Chinese, Delphi expert consultations (n = 5) for cultural adaptation, and a cross-sectional study (n = 149) for validation. Results The C-ISC-Q has 24 items and four dimensions. The critical ratio of each item is over 3.0, and the correlation coefficient between each item and the scale’s total score is above 0.4. The Cronbach’s α value for the scale is 0.930, and for each dimension, it is between 0.870–0.92. The retest reliability for the scale is 0.894, and for each dimension is between 0.751–0.889. The content validity at the item level ranges from 0.8~1.0, and at the scale level is 0.9. The criterion-related validity of the scale was −0.708, and the correlation for each dimension was 0.329–0.624. The principal component analysis identified four common factors, with a cumulative contribution rate of 67.846%. Conclusions The C-ISC-Q is culturally sensitive, reliable, and valid to measure the quality of life for patients with NB. It can assist nurses and researchers in tailoring strategies to enhance the quality of life for patients with NB.
Keywords: Intermittent self-catheterization; Reliability; Validity; Cross-cultural adaptation; Neurogenic bladder